SAT0514 Does Hyperuricemia Worsen Pain and Function in Patients with Knee or Hip OA? Results from the Khoala Cohort. (10th June 2014) - Ea, H.K.; Rat, A.C.; Sellam, J.; Fellahi, S.; Bastard, J.-P.; Bernard, L.; Chevalier, X.; Capeau, J.; Berenbaum, F.; Guillemin, F.; Richette, P.
Abstract : Background: Several reports have found an association between gout and osteoarthritis (OA). Urate levels in OA synovial fluid has been shown to associate with both knee OA severity and production of proinflammatory cytokines. However, the impact of serum urate (SUA) levels on pain and disability or radiographic damages in patients with established knee or hip OA remains unknown Objectives: To search for an association between SUA levels and OA severity and OA symptoms in a cross-sectional analysis of a large cohort of patients Methods: Data are from 863 subjects with knee or hip OA from the KHOALA (Knee and Hip Osteo-Arthritis Long-Term Assessment) cohort. For each patient, SUA, CRPus, serum adipokines and lipids levels were assessed at inclusion. Baseline clinical data included the WOMAC (total, pain, stiffness and function) and the Harris, the IKS and Osteoarthritis Knee and Hip Quality of Life ( OAKHQOL ) scores. Associations between SUA levels and OA symptoms and disability was searched using uni and multivariate linear regression and associations between SUA levels and the presence of one or more radiographic OA with multivariate logistic regression. Results: 863 patients (69.1% women) were included. Mean age was 61.9 (±8.5) years and mean BMI 29.4 (±6) kg/m 2 . 87 (10.1%) patients had diabetes. OA involved uni- or bilateral knees in 653 patients and uni- or bilateral hip in 286 patients. Mean SUA levels was 340 μmol/l (range 110.0-910.0). Hyperuricemia (SUA >360 μmol/l) was observed in 305 (35.3%) patients. The level of uricemia was weakly correlated with BMI (r=0.23), insulinemia (r=0.273) and the triglycerides level (r=0.296). SUA levels did not significantly correlate with the WOMAC, the Harris, the IKS or the OAKHQOL scores in patients with either symptomatic knee or hip OA. In addition, SUA was not associated with the number of symptomatic knee or hip OA joints or radiographic knee or hip OA joints Conclusions: In this large cohort of patients with knee or hip OA, SUA levels were not associated with OA symptoms, severity or radiographic damages. Such results do not exclude a prognostic value of SUA on OA progression. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3864